Proteomic analysis of the humoral antifungal immune response of the soft tick,Ornithodoros savignyi Audouin (1827) - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.